The Effect of Good Corporate Governance, Interest Rate, and Inflation on Islamic Stock Prices - Wijaya, Herman; Maulita, Dian; Salsabila, Nisrina; Azahra, Najwa (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2026)
This study aims to examine the effect of corporate governance mechanisms and macroeconomic factors on the trading values of Shariah-compliant stocks. The governance variables include independent board representation, institutional ownership, managerial ownership, and audit committees, while the macroeconomic variables include inflation and interest rates. The research adopts a quantitative associative approach, using stock value as the dependent variable. The sample comprises 30 manufacturing companies listed on the Indonesia Stock Exchange (IDX) and included in the Jakarta Islamic Index (JII) during the 2020–2024 period, resulting in 150 annual financial statements. Data were obtained from secondary sources, selected purposively, and analyzed using multiple linear regression at the 5% significance level. The results show that independent directors, institutional ownership, managerial ownership, and audit committees do not have a significant effect on Shariah stock prices, indicating that internal corporate governance mechanisms have not effectively influenced market valuation. In contrast, inflation and interest rates have a significant negative effect on Shariah stock prices, as rising prices and higher borrowing costs reduce profitability and investor interest. These findings suggest that macroeconomic conditions play a more dominant role than internal governance factors in determining Shariah stock performance. Therefore, investors should pay closer attention to inflation and interest rate movements. At the same time, regulators and management should focus on maintaining economic stability and improving corporate governance effectiveness to enhance market confidence.